AIR FLOW CONTROL FACTORS IN PNEUMATIC TRANSPORT DEVICE - Kholmirzaev, Farxod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article examines the possibilities of maintaining the initial quality parameters of raw cotton and increasing productivity by improving the air flow control device in pneumatic transport.